Pengadaan Sumur Resapan Sebagai Salah Satu Usaha Konservasi Air Tanah Di Kampung Babakan Cikeruh Cimekar Cileunyi Bandung - Riyanto Adji (Journal of Environmental Engineering and Waste Management, 2020)
Kampung Babakan Cikeruh is a slope or ridge area , a few years ago this area did not experience any difficulty in water availability because the land had not yet changed its function, Since the development of the land conversion function as a housing area, it has caused a decrease in the ground water level in the dry season, so that it becomes a problem for residents because residents rely on wells to be a source of water for household needs every day. Based on these conditions, it is necessary to have groundwater conservation measures at the study site, so that groundwater level subsidence is not deep. The research methodology used to identify the problem, then determine the scope of the problem, conduct a literature review that is relevant to the problem under study, so that the formulation of the theoretical framework, hypotheses and conceptual concepts of the solution to the problem being examined, then make the method of conducting research including determining the location, gathering data and analysis, so as to produce solutions to the problems studied and researchers will provide conclusions. The researcher provides a solution in the form of leach absorption wells, and from 10 wells examined, the researcher makes infiltration wells that are between 3 adjacent wells and the results obtained 3 wells have a stable ground water level in the dry season. the conclusion is the effort to conserve water to maintain the stability of the ground water level in the dry season by making infiltration wells.